The Politics of Northern Ireland - McEvoy, Joanne (Edinburgh University Press, 2022)
GBS_insertPreviewButtonPopup('ISBN:9780748625017');The political scene in Northern Ireland is constantly evolving. This book reflects the most recent changes and synthesises some of the best thinking on the subject. It provides an overview of the politics of Northern Ireland, including detailed coverage of the institutional structure under the Good Friday Agreement and an evaluation of how the institutions operated in practice.Opening with the historical context and discussion of the nature of the conflict, the standpoints of unionism, nationalism, loyalism and republicanism are explored. The evolution of political initiatives since the 1970s is traced, leading to the peace process of the 1990s and culminating in the Good Friday Agreement in 1998. The period of devolution in Northern Ireland (1999-2002) is evaluated, and the book concludes with coverage of political developments post-suspension, paying particular attention to the on-going debate on changes to the Agreement and the prospects for power-sharing.Key FeaturesPresents an impartial view of Northern Irish politicsGives readers the confidence to use some of the more complicated political concepts in their study of the subjectEncourages readers to analyse, question and discuss Northern Irish politics
Description based on online resource; title from PDF title page (publisher's Web site, viewed 02. Mrz 2022)
Keywords: Politics; POLITICAL SCIENCE / General; Peace-building -- Northern Ireland